FGF2-induced STAT3 activation regulates pathologic neovascularization. (October 2019) - Dong, Zhenyu; Santeford, Andrea; Ban, Norimitsu; Lee, Tae Jun; Smith, Craig; Ornitz, David M.; Apte, Rajendra S.
Abstract: Cell-autonomous endothelial cell (EC) fibroblast growth factor receptor (FGFR) signaling through FGFR1/2 is essential for injury-induced wound vascularization and pathologic neovascularization as in blinding eye diseases such as age-related macular degeneration. Which FGF ligand(s) is critical in regulating angiogenesis is unknown. Utilizing ex vivo models of choroidal endothelial sprouting and in vivo models of choroidal neovascularization (CNV), we demonstrate here that only FGF2 is the essential ligand. Though FGF-FGFR signaling can activate multiple intracellular signaling pathways, we show that FGF2 regulates pathogenic angiogenesis via STAT3 activation. The identification of FGF2 as a critical mediator in aberrant neovascularization provides a new opportunity for developing multi-target therapies in blinding eye diseases especially given the limitations of anti-VEGF monotherapy. Highlights: Fibroblast growth factor-2 (FGF-2) regulates choroidal neovascularization. FGF-2 activates intracellular stat3. The identification of the fgf-2/stat3 axis presents novel therapeutic opportunities.